The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/207239
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Impact of ZnS Nanoparticles on Daphnia sp. in the Western Part (Districts of Bankura and Purulia) of West Bengal, India

Abstract: ZnS nanoparticles of different sizes are synthesized employing a simple wet chemical method. These nanoparticles are used to study their impact on the Daphnia sp. through traditional toxicity tests. The percentage of mortality is found to increase initially with increasing nanoparticle concentration or exposure time and is finally found to saturate for higher concentrations or exposure times. Mortality is found to be higher for smaller particles. Hopping frequency and heart rate are also found to increase with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The increased production and wide applications of nanoparticles are making it more likely that such materials will end up in watercourses, either as medical or industrial waste, or when used as ecological tools with unknown consequences for aquatic life. Recent studies (Smith et al 2007;Oberdorster 2004;Koziara et al 2003;Zhu et al 2006;Bhattacharjee et al 2013;Griffitt et al 2007;Fedirici et al 2007) (5-11) have thrown some light on the adverse effect of nanoparticles on aquatic fauna. Carbon nano-tubes are found to be a respiratory toxicant in rainbow trout (Smith et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased production and wide applications of nanoparticles are making it more likely that such materials will end up in watercourses, either as medical or industrial waste, or when used as ecological tools with unknown consequences for aquatic life. Recent studies (Smith et al 2007;Oberdorster 2004;Koziara et al 2003;Zhu et al 2006;Bhattacharjee et al 2013;Griffitt et al 2007;Fedirici et al 2007) (5-11) have thrown some light on the adverse effect of nanoparticles on aquatic fauna. Carbon nano-tubes are found to be a respiratory toxicant in rainbow trout (Smith et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ZnS nanoparticles are shown to be harmful for Daphnia sp. (Bhattacharjee et al 2013) by reducing the dissolved oxygen content in water due to enhanced surface photo-oxidation associated with its nanoparticle nature. It is found that copper nanoparticles harm gills of Zebra fish (Danio rerio) through an unknown mechanism, which is different from that of dissolved copper ions (Griffitt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Water may dissolve a part of the SO 2 released in the process causing reduction in the pH value of the water [12,26]. Subsequently under the exposure of ZnS NPs, the aquatic fauna of that particular habitat were forced to live in an oxygen depleted and acidified atmosphere [11,12,[20][21][22][23][24][25][26].…”
Section: Results and Discussion:-zns Np Induced Hypoxia And Environmmentioning
confidence: 99%
“…The ZnS NPs are prepared by simple wet chemical method using zinc nitrate hexahydrate [Zn(NO 3 ) 2 ⋅6H 2 O] as zinc precursor and sodium sulphide (Na 2 S) as sulphur precursor [12,25].The as precipitated nanoparticles were filtered out and were washed for several times in distilled water and absolute alcohol (100% ethanol) and then were dried at 30∘C in a vacuum oven. The nanoparticles were characterized using X-ray diffraction study (XRD), Transmission Electron Microscopy (TEM), Particle Size Analysis (PSA), Energy dispersive X-ray study (EDX), and X-ray Photoelectron Spectroscopy (XPS).…”
Section: Experimental:-preparation and Characterization Of Zns Nanopamentioning
confidence: 99%
See 1 more Smart Citation